BUYING INTEREST AND TRUST MODEL: E-WOM AND BRAND IMAGE - Muhammad Reza Putra; Gupron Gupron (Dinasti Publisher, 2020)
The article Buying Interest and Trust Model: E-Wom Analysis and Brand Image aims to build a research hypothesis using the library research method. To find out the variables that affect Buying Interest Online, a review of previous studies was conducted. The results of this article indicate a hypothesis has been built for further research that e-WOM, and Brand Image, have an effect on Online Purchase Trust and Interest.